A festa de São Sebastião na Comunidade de Bocaina : dimensões da identidade e da memória - Lima, Thamara Luiza da Silva e (2024)
Considering the wealth and dynamism in Brazilian cultural heritage and, mainly, the importance of studies and differentiated social actions in favor of safeguarding cultural assets such as saint9s festival, this dissertation highlights the experiences at the festival of São Sebastião in the community of Bocaina in Santo Antonio de Leverger, Mato Grosso (MT), from the introduction of this cult in the community due to the devotion of some families. The patron saint9s devotion and the devotional manifestations associated with the cult went beyond the boundaries of the community through a tradition that has been maintained over time. Throughout its structuring process, this festival has undergone significant changes, becoming a milestone in the Bocaina calendar and its most prominent and religious manifestation. Taking into account the importance of the São Sebastião festival as a celebration for the history and culture in the Bocaina Community, the research aimed at analyzing the festival as a constituent of their identity in the municipality of Santo Antônio de Leverger-MT. Among the aspects analyzed, its experiences and memories representativeness stand out among the collective and the factors that made it possible to preserve its perpetuity, despite the changes. Considering the questions raised by it, the perspectives for its analysis were open by an intermediate path between the two history fields: Cultural and social. The theoretical referential used, supported in oral e decolonial history, contributed to the interpretative journey. The research was done under a qualitative approach, using methods such as bibliographic, documental and oral history, including interviews with the dwellers, partygoers and devotees, analyzing their experiences with the devotion.